2022
DOI: 10.3390/ijerph191711020
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Teachers: Validation of the Spanish Version of the CD-RISC10© Scale in Early Childhood, Primary and Special Education Teachers

Abstract: Schools are a fundamental context for processes of promotion and generation of resilience, since they focus not only on aspects of academic development, but also of personal and social development. Resilience in the teacher has a dual function. On the one hand, as resilient professionals, teachers can foster the development of resilience in their students; on the other hand, teaching resilience facilitates their own personal and professional well-being. Despite research highlighting the benefits of resilience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Novice teachers (with up to 5 years of teaching experience) show lower levels of resilience and mindfulness compared to those with the longest tenure. These results are consistent with the findings of Flores-Buils, Caballer-Miedes, and Mateu-Pérez (2022), who assumed that more experienced teachers have more opportunities to develop resilience in school than other teachers with less experience. Associations with mindfulness have been shown to be more complex.…”
Section: Discussionsupporting
confidence: 92%
“…Novice teachers (with up to 5 years of teaching experience) show lower levels of resilience and mindfulness compared to those with the longest tenure. These results are consistent with the findings of Flores-Buils, Caballer-Miedes, and Mateu-Pérez (2022), who assumed that more experienced teachers have more opportunities to develop resilience in school than other teachers with less experience. Associations with mindfulness have been shown to be more complex.…”
Section: Discussionsupporting
confidence: 92%
“…In the international literature, studies on special education teachers have found that, among educators, special education teachers exhibit lower levels of resilience, likely due to their exposure to various challenging situations (Flores-Buils et al, 2022). In the Greek context, Botou and her colleagues (2017) found that Greek teacher's resilience is very highly correlated to their relationships with family and colleagues.…”
Section: Journal Of School and Educational Psychologymentioning
confidence: 99%
“…In this respect, students’ integral development is considered to be fundamental, i.e., the commitment of teachers to the personal, social, and emotional development of children so that they can adapt to different situations in the present and future, and not just to a focus on acquiring academic knowledge. Therefore, the school should promote resilience [ 36 , 37 , 38 ]. Thus, teachers can be role models as they are often significant figures, being among the primary caregivers and sharing a significant amount of time with each child.…”
Section: Introductionmentioning
confidence: 99%